HIPOTIROID SEBAGAI PEMICU GANGGUAN IRAMA JANTUNG: SEBUAH LAPORAN KASUS VENTRIKULAR TAKIKARDIA PADA PASIEN HIPOTIROID - Sahlan Abadi; Indra Prasetya (RSUD Dr. Saiful Anwar Province of East Java, 2026)
Hypothyroidism was associated with bradyarrhythmia, conduction abnormalities, impaired myocardial function, and ventricular arrhythmia. The prevalence of ventricular tachycardia in hypothyroid was 2.6%. The patient was a 52-year-old woman who was experiencing palpitations, blurred vision, and syncope. ECG showed ventricular tachycardia (VT). Laboratory tests showed increased TSH and decreased T3 and FT4. Echocardiography showed global normokinetic, normal LV systolic function (EF 57%), normal RV systolic function, and normal heart chamber dimensions. DCA evaluation showed normal coronary artery. The patient underwent ablation of frequent PVCs originating from the anteroseptal RVOT. After ablation and hypothyroid treatment, there were no more VT episodes. The pathophysiological mechanism underlying the relationship between hypothyroidism and cardiac arrhythmias was the regulatory effect of thyroid hormones on cardiovascular hemodynamics and cardiac ion channels. Thyroid hormones directly regulate the function of ion channels such as sodium, calcium, and potassium channels. Ion channel dysfunction can prolong ventricular repolarization, which can trigger VT. This case report demonstrates the potential danger of thyroid dysfunction, especially hypothyroidism, in causing VT. Timely identification and treatment of hypothyroidism can prevent recurrence of arrhythmia and improve cardiac function.